2016
DOI: 10.3390/ijerph13100948
|View full text |Cite
|
Sign up to set email alerts
|

The Health, Enlightenment, Awareness, and Living (HEAL) Intervention: Outcome of an HIV and Hepatitis B and C Risk Reduction Intervention

Abstract: African American women have among the highest HIV/AIDS and hepatitis B and C incidence rates in the United States, especially among those homeless or incarcerated. The objective of this study was to evaluate the Health Enlightenment, Awareness and Living Intervention, designed to decrease HIV/AIDS, hepatitis and related risky behaviors. The thirteen-session intervention was implemented among homeless and formerly incarcerated low-income African American women, ages 18 to 55, in Atlanta, Georgia from 2006 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The 36 studies were published between 1999 and 2020. Thirty‐one (31) were based in the United States (Akiyama et al, 2019; Binswanger et al, 2015; Clayton et al, 2013; Costa et al, 2018; Farabee et al, 2016; Fox, Anderson, Bartlett, Valverde, MacDonald, et al, 2014; Fox, Anderson, Bartlett, Valverde, Starrels, & Cunningham, 2014; Gordon et al, 2018; Hartwell & Orr, 1999; Hawks et al, 2016; Henry‐Akintobi et al, 2016; Jacob Arriola et al, 2007; Johnson et al, 2014; Khawcharoenporn et al, 2019; Koester et al, 2014; Kuo et al, 2019; Lamberti et al, 2017; Leukefeld et al, 2012; MacGowan et al, 2015; Morse et al, 2017; Needels et al, 2005; Nunn et al, 2010; Nyamathi et al, 2017; Rasch et al, 2013; Reznick et al, 2013; Shavit et al, 2017; Thomas et al, 2019; Wang et al, 2012, 2019; Windsor et al, 2014; Zaller et al, 2008), one in Puerto Rico (Wiersema et al, 2020) and two (2) each in Canada (Matheson et al, 2011; McLeod et al, 2020) and the United Kingdom (Ball et al, 2013; Newbury‐Birch et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 36 studies were published between 1999 and 2020. Thirty‐one (31) were based in the United States (Akiyama et al, 2019; Binswanger et al, 2015; Clayton et al, 2013; Costa et al, 2018; Farabee et al, 2016; Fox, Anderson, Bartlett, Valverde, MacDonald, et al, 2014; Fox, Anderson, Bartlett, Valverde, Starrels, & Cunningham, 2014; Gordon et al, 2018; Hartwell & Orr, 1999; Hawks et al, 2016; Henry‐Akintobi et al, 2016; Jacob Arriola et al, 2007; Johnson et al, 2014; Khawcharoenporn et al, 2019; Koester et al, 2014; Kuo et al, 2019; Lamberti et al, 2017; Leukefeld et al, 2012; MacGowan et al, 2015; Morse et al, 2017; Needels et al, 2005; Nunn et al, 2010; Nyamathi et al, 2017; Rasch et al, 2013; Reznick et al, 2013; Shavit et al, 2017; Thomas et al, 2019; Wang et al, 2012, 2019; Windsor et al, 2014; Zaller et al, 2008), one in Puerto Rico (Wiersema et al, 2020) and two (2) each in Canada (Matheson et al, 2011; McLeod et al, 2020) and the United Kingdom (Ball et al, 2013; Newbury‐Birch et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Study designs included four (4) qualitative studies (Koester et al, 2014; McLeod et al, 2020; Nunn et al, 2010; Thomas et al, 2019), fourteen (14) randomised control trials (Clayton et al, 2013; Farabee et al, 2016; Gordon et al, 2018; Khawcharoenporn et al, 2019; Kuo et al, 2019; Lamberti et al, 2017; Leukefeld et al, 2012; MacGowan et al, 2015; Needels et al, 2005; Newbury‐Birch et al, 2014; Nyamathi et al, 2017; Reznick et al, 2013; Wang et al, 2012; Zaller et al, 2008) and one (1) single‐arm trial (Akiyama et al, 2019), fourteen (14) cohort or survey studies (Ball et al, 2013; Costa et al, 2018; Fox, Anderson, Bartlett, Valverde, MacDonald, et al, 2014; Fox, Anderson, Bartlett, Valverde, Starrels, & Cunningham, 2014; Hartwell & Orr, 1999; Hawks et al, 2016; Henry‐Akintobi et al, 2016; Jacob Arriola et al, 2007; Matheson et al, 2011; Morse et al, 2017; Rasch et al, 2013; Shavit et al, 2017; Wang et al, 2019; Wiersema et al, 2020), two (2) pilot or feasibility studies (Binswanger et al, 2015; Johnson et al, 2014) and one (1) using mixed qualitative and quantitative methods (Windsor et al, 2014). Sample sizes varied from 13 to 1410 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior qualitative research has identified challenges PEH experience navigating complex systems (Henwood et al, 2018;Moore-Nadler et al, 2020). However, nurse-led programs have been shown to be successful in treating those unstably housed with HCV (Harney et al, 2019;O'Sullivan et al, 2020) as have patient-centered approaches involving extensive HCV education (Henry-Akintobi et al, 2016).…”
Section: Structural-level Needs To Consider When Designing Hcv Interventionsmentioning
confidence: 99%
“…The HIV-related stigma and housing insecurity produced direct effects upon depressiveness, apathy and social support avenues, and HIV-related stigma caused a direct effect on self-rated health [5]. (iv) In a group of homeless and formerly imprisoned low-income level Afro-American women, aged from 18 to 55 years, residing in Atlanta, Georgia, USA, it was observed that following a thirteen session intervention program, there were marked elevations in hepatitis B and C knowledge-over-time, concurrent with reductions in unprotected sexual incursions in exchange for money, drugs and/or shelter, sex under the influence of drugs or alcohol [6]. The impressive findings from this and similar studies underline the paucity and insufficiency of preventional efforts under pre-existing conditions with particular regard to the emphasis placed here on 'enlightenment' and 'awareness' .…”
Section: Editorialmentioning
confidence: 99%